2018
DOI: 10.1002/mcf2.10031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hook and Bait Size on Catch Efficiency in the Persian Gulf Recreational Fisheries

Abstract: The effect of hook and bait sizes on the catch efficiency and size composition of Spangled Emperor Lethrinus nebulosus, Orange-spotted Grouper Epinephelus coioides, and Narrowbarred Mackerel Scomberomorus commerson was investigated in the recreational and semi-subsistence handline fishery in the Persian Gulf. Based on expectations that increasing hook and bait sizes would decrease the catch efficiency of the smaller individuals while maintaining the catch efficiency of larger fish, we investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This study evinced that size of L. mysteceus and L. esocinus caught by angling from the Keban Dam Lake was a function of lures size, which are in line with findings of previous studies (Arlinghaus et al, 2008;Eighani et al, 2018;Orsi, 1987). This study found that increasing lure size substantially reduces the catch rate of undersized fishes, which are consistent with the previous findings for other fish species (Alós et al, 2008;Ateşşahin et al, 2015;Herrmann et al, 2018;Otway & Craig, 1993). In this study, a significant relationship was also detected between the lures colour and size structure of L. mysteceus though this relationship was not significant in L. mysteceus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study evinced that size of L. mysteceus and L. esocinus caught by angling from the Keban Dam Lake was a function of lures size, which are in line with findings of previous studies (Arlinghaus et al, 2008;Eighani et al, 2018;Orsi, 1987). This study found that increasing lure size substantially reduces the catch rate of undersized fishes, which are consistent with the previous findings for other fish species (Alós et al, 2008;Ateşşahin et al, 2015;Herrmann et al, 2018;Otway & Craig, 1993). In this study, a significant relationship was also detected between the lures colour and size structure of L. mysteceus though this relationship was not significant in L. mysteceus.…”
Section: Discussionsupporting
confidence: 92%
“…. Accordingly, the use of larger hooks can also substantially reduce the catch rates of undersized fish (Alós et al, 2008;Ateşşahin et al, 2015;Herrmann et al, 2018;Otway & Craig, 1993).…”
mentioning
confidence: 99%
“…Using the numbers and sizes of snow crabs caught in test and standard pots in each set, we determined whether there was a significant difference in the catch efficiency averaged over deployments between the test pot and standard pot types. Specifically, we assessed the relative length-dependent catch efficiency effect of changing from standard pots to moon pots using the method described in Herrmann et al [31] and compared the catch data for the standard and the test pots. This method models the size-dependent catch comparison rate ( CC w ) summed over sets: where ns wj and nt wj are the numbers of snow crabs caught in each size class w in a standard pot and a test pot in set j .…”
Section: Methodsmentioning
confidence: 99%
“…The confidence intervals for the catch comparison curve and catch ratio curve were estimated using a double bootstrapping method [31, 34]. This bootstrapping method accounts for between-set variability (the uncertainty in the estimation resulting from set variation of catch efficiency in the pots and in the availability of snow crabs) as well as within-set variability (uncertainty about the size structure of the catch for the individual sets).…”
Section: Methodsmentioning
confidence: 99%
“…The results indicate that seasonality partly influenced the catch rates of swordfish in the Kenyan coastal waters. This temporal distribution of the swordfish catches and abundance could be partly attributed to the seasonal changes in the temperature of the sea water, sex and size of the individual fish, and availability of food in the environment (Mueni et al, 2019;Lan et al, 2014;and Ward and Elscot, 2000) and the type of fishing gears (Herrmann et al, 2018;and Tuda et al, 2016). The high catch rates seem to coincide with the spawning season (October through to April) for swordfish in the Indian Ocean (Lan et al, 2014;and IOTC, 2017).…”
Section: Temporal Variation In Swordfish Catchesmentioning
confidence: 99%